ظاهرة تدريس الأصوات العربية - Albarra Sarbaini (Institut Agama Islam Negeri (IAIN) Metro, 2017)
A language is made up of units of units of a particular sound, with the sound unit up unit formed millions and millions of words in diverse situations. Each language is a bona fide treasures of the selected sound from all possible sounds that can be spoken man, which may differ from other treasures of the sounds of language. Arabic sounds denoted by